Facile longitudinal unzipping of carbon nanotubes to graphene nanoribbons and their effects on LiMn2O4 cathodes in rechargeable lithium-ion batteries. (November 2015) - Ilango, P. Robert; Prasanna, K.; Subburaj, T.; Jo, Yong Nam; Lee, Chang Woo
Graphical abstract: Highlights: The graphene nanoribbons are successfully synthesized by chemical unzipping method. The LiMn2 O4 is surface modified with graphene nanoribbons via ultrasonic-assisted wet-coating. The electrochemical effects of graphene nanoribbons on LiMn2 O4 are studied. The modified LiMn2 O4 shows the good electronic conductivity and improved capacity. Abstract: A LiMn2 O4 cathode has been surface-modified with carbon nanotubes and graphene nanoribbons via an ultrasonic-assisted wet-coating method. The structural stability of the surface-modified LiMn2 O4 and the amorphous nature of the coated carbon materials are confirmed using X-ray diffraction (XRD). Field emission scanning electron microscopy (FE-SEM) reveals the strong and uniform distribution of graphene nanoribbons over the LiMn2 O4 in comparison to the carbon nanotubes-coated LiMn2 O4 . Furthermore, field emission transmission electron microscopy (FE-TEM) confirms the strong adhesion of a smooth, sheet-like graphene nanoribbons layer over the LiMn2 O4 surface, whereas the carbon nanotubes are observed to have weak and/or irregular contact with LiMn2 O4 . Electrochemical studies have been carried out by electrochemical impedance spectroscopy (EIS), cyclic voltammetry (CV), and a galvanostatic cycler. The graphene nanoribbons-modified LiMn2 O4 cathode shows better electrochemical properties in terms of a suppressed charge transfer resistance, high current density, negative shift in polarization, longer calendar life, and high rate capabilities. In addition, the graphene nanoribbons-modified LiMn2 O4 delivered 90% of the retention capacity after 50 cycles at a rate of 1 C with the potential limits of 3.0–4.5 V vs. Li/Li + .